Effects of Psychological Contract Breach Among University Employees in Pakistan: Moderating Role of Perceived Organisational Support - Rana Humayun, Ihsan (Universiti Malaysia Sarawak (UNIMAS), 2020)
Psychological contract is globally considered a framework to understand the employee-employer relationship. Breach of psychological contract leads to negative attitudes and behaviours. This thesis investigated the effects of psychological contract breach among university employees in Pakistan by using perceived organisational support as the moderating role, which has not been widely studies. This study was conducted using a sampling frame of five universities in Pakistan. Fish-bowl sampling technique was used and 1,230 university employees were used as the sample size for data collection with 739 participants taking part in this study. The data were analysed by using SPSS and AMOS (V-22) and structural equation modelling technique was used for data analyses. Reliability, validity, exploratory, confirmatory and moderation analyses were performed. The data showed that psychological contract breach led to turnover intention, job dissatisfaction and counterproductive work behaviour among university employees in Pakistan. The data results also showed that perceived organisational support moderated the relationship between psychological contract breach and turnover intention; whereas no moderation was shown between the relationship of psychological contract breach and job dissatisfaction and counterproductive work behaviour, which left a gap for future investigation. The results showed that the employees were found to be facing psychological contract breach regardless of qualification, age and gender. Keywords: Psychological contract breach & perceived organisational support, job dissatisfaction, turnover intention, counterproductive work behaviour, structural equation modelling.